A geometrically nonlinear isogeometric model for multilayered microplates under thermo-mechanical load and its application to flexible organic solar cells. (1st February 2022) - Liu, Shuo; Wang, Kaifa; Wang, Baolin; Li, Jine; Zhang, Chunwei
Abstract: This paper formultes a thermo-mechanical nonlinear bending model of multilayered microplates with size effects. The model simultaneously includes the effects of geometrically nonlinear, isogeometric parameter,  and the higher order shear deformation of the plate. Based on the proposed model, the geometrically nonlinear bending behaviors of a flexible organic solar cell (OSC) that have five different layers under the photo-thermal and wind load are investigated. Both the uniform and non-uniform temperature fileds along the thickness direction of the plate are discussed. Results show that the size effects reduce the normalized deflections remarkably. Significantly, as the thickness downs to the characteristic size of the material length scale parameter, the deflection can decrease as much as 75%. Subsequently, as the wind speed increases, the impact of the small-scale effect becomes increasingly significant. A semi-empirical formula for the relationship between the tensile stress and solar irradiation of the layers is derived. The optimal solar irradiation and the efficiency of the OSC are obtained.